A Survey of Physical Fitness Levels Among Overweight Elementary School Students (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
The increasing prevalence of overweight among school-aged children poses a significant public health concern, particularly due to its negative impact on physical fitness and overall well-being. This study aims to assess the physical fitness levels of overweight elementary school students aged 10–12 years at SDIT Nurul Rahmah Kemayoran and SDS Muhammadiyah 1 Bangkalan. A descriptive quantitative method with a survey approach was employed, using standardised fitness tests including sit-ups, pull-ups (hanging), vertical jump, 40-meter sprint, and 600-meter run. The results showed that most students performed well in the sit-up test, indicating adequate abdominal strength. However, their performance in other tests—especially in cardiovascular endurance (600-meter run), speed (40-meter sprint), and leg explosive power (vertical jump)—was predominantly in the “Poor” and “Very Poor” categories. Overall, the majority of overweight students demonstrated low levels of physical fitness. These findings highlight the need for schools and families to promote structured physical activities and healthier lifestyles to improve children’s fitness and prevent long-term health risks associated with being overweight.